VD_FINDINFO Jug / 2011 / 105 vom 8. Februar 2011 - VD Tribunal cantonal (2011)
UTILISATION FRAUDULEUSE D'UN ORDINATEUR, PEINE, ATTÉNUATION DE LA PEINE | 147 al. 2 CP, 47 CP, 398 al. 3 let. a CPP (CH), 398 al. 3 let. b CPP (CH), 399 al. 3 CPP (CH), 399 al. 4 CPP (CH)